Hereditary Hemorrhagic Telangiectasia - a literature review - Stodolak, Marcel; Krużel, Aleksandra; Kłos, Kamil; Sajdak, Piotr; Tomasik, Justyna; Dębik, Marika; Szydłowski, Łukasz; Żurowska, Klaudia; Ziajor, Seweryn; Bednarski, Artur; Turski, Mikołaj (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Hereditary hemorrhagic telangiectasia (HHT), also known as Osler-Weber-Rendu syndrome, is a rare and complex vascular disorder characterized by abnormal blood vessel formation. It can present significant challenges in diagnosis and management, as it is currently estimated up to 90% of those affected are never diagnosed. Despite its rarity, HHT can carry substantial implications for patients and their families, at times requiring comprehensive medical care and support. This paper aims to provide an in-depth exploration of HHT, encompassing its epidemiology, genetics, clinical manifestations, diagnostic approaches, and current management strategies. Moreover, we hope to point out possible areas in need of future research. Description of the state knowledge: HHT is an autosomal dominant genetic disorder that affects 1 in 5-10,000 people. Its most prominent symptoms include telangiectasia of skin and mucous membranes, recurrent epistaxis, gastrointestinal bleeding and arteriovenous malformations in vital organs. In the vast majority of cases, it is caused by a mutation in one of the following genes: ENG, ACVRL1, SMAD4; however, mutations in other genes have been described to cause a similar or much the same constellation of symptoms. Treatment options are focused on managing symptoms and improving quality of life, but possible new treatment options are being researched that could change the landscape of HHT management. Summary: HHT is a severely underdiagnosed disease that has seen a surge of researchers’ interest in recent years. We firmly believe that, combined with plummeting costs of genetic testing and possible new treatment options, means that HHT will become increasingly important in physicians’ everyday practice.